Rumen Degradability and In Vitro Fermentation Characteristics of Various Cereal Grains - Santhosh Reddy, V.; Nagalakshmi, D.; Venkateswarlu, M.; Suresh Rathod, (Indian Journal of Animal Nutrition, 2022)
A study was conducted to evaluate the in vitro gas production (IVGP), degradability and fermentation characteristics of various cereal grains viz., maize, broken rice, jowar, ragi, wheat, barley and bajra by in vitro gas production technique.The in vitro gas production technique conducted indicated significant (P< 0.01) variation for cereal grains with regard to in vitro gas produced (IVGP) volume, in vitro dry matter degradability (IVDMD %), in vitro organic matter degradability (IVOMD %) and in vitro neutral detergent fibre degradability (IVNDFD %). The IVGP and IVOMD were highest for wheat and barley followed by bajra and lowest for maize, broken rice, jowar and ragi. The order of the IVDMD % from highest to lowest was broken rice> wheat>jowar and maize>bajra>barley>ragi. The IVNDFD (%) was highest for wheat and barley followed by bajra then by ragi and lowest in jowar, broken rice and maize. The partitioning factor was higher (P< 0.01) in broken rice, jowar and maize, followed by ragi, then bajra and was lowest in wheat and barley. The microbial biomass production (MBP) (mg/500mg) was lowest (P< 0.01) in maize, broken rice, jowar and ragi, followed by bajra and highest in wheat and barley. The efficiency of microbial biomass production (EMBP) (g/kg DOM) was higher (P< 0.01) and comparable for broken rice, maize and jowar followed by ragi and then bajra and lowest was from barley and wheat. The ME values from in vitro study varied significantly (P< 0.01) and in descending order was wheat >barley >bajra>broken rice >jowar and maize >ragi. The pH was highest (P> 0.01) in maize and jowar and comparable with broken rice and bajra, followed by ragi and lowest was for wheat and barley. The NH3-N concentration from various cereal grains did not vary, but total volatile fatty acid production was significant. The highest (P< 0.01) TVFA production was from wheat, followed by barley then bajra, jowar and lowest in maize, broken rice and ragi.